2020
DOI: 10.3168/jds.2019-17700
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a synbiotic yogurt using monk fruit extract as sweetener on glucose regulation and gut microbiota in rats with type 2 diabetes mellitus

Abstract: We developed a synbiotic yogurt using monk fruit extract as a sweetener and investigated the effects of feeding the yogurt to rats with type 2 diabetes induced by streptozotocin and a high-fat diet. The rats fed the synbiotic yogurt showed greater blood glucose regulation and a significant decrease in insulin resistance and glycosylated hemoglobin compared with rats fed yogurt sweetened with sucrose, and they showed a remarkable improvement in short-chain fatty acid levels and gut microbiota status. Liver and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Monk fruit extract (MFE) consists of a group of triterpenoid glycosides, which are regarded as the main active components of the sweet taste and responsible for the main biological functions of monk fruit. Monk fruit has been shown to have health benefits including antitussive, antiasthmatic, antioxidative, liver-protective, glucose-lowering, immunoregulation, and possibly anticarcinogenic properties (Ban et al, 2020). MFE has been used as a sweetener in China, Japan, and the United States, and it is a suitable and safe low-calorie sweetener for people with type 2 diabetes (Qi et al, 2008;Zhou et al, 2009;Xu et al, 2015;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Monk fruit extract (MFE) consists of a group of triterpenoid glycosides, which are regarded as the main active components of the sweet taste and responsible for the main biological functions of monk fruit. Monk fruit has been shown to have health benefits including antitussive, antiasthmatic, antioxidative, liver-protective, glucose-lowering, immunoregulation, and possibly anticarcinogenic properties (Ban et al, 2020). MFE has been used as a sweetener in China, Japan, and the United States, and it is a suitable and safe low-calorie sweetener for people with type 2 diabetes (Qi et al, 2008;Zhou et al, 2009;Xu et al, 2015;Zhou et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Similar results were also investigated in the latest study, additive of monk fruit extract in yogurt increased the relative abundance of Bacteroidetes and reduced Firmicutes and regulated blood glucose in rats with T2DM. 23 Recently, a large-scale population study of gut microbiota showed that the majority of Proteobacteria were positively correlated to the occurrence of metabolic syndrome while most Bacteroidetes were more prevalent in healthy individuals, 24 indicating the potential health functions of MV through the modulation of the gut microbiota composition. At the genus level (Figure 2C), the taxa were mainly Bacteroides, Megamonas, Bif idobacterium, Prevotella, Blautia, and so on.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The CY group received sucrose by orally feeding on 30 mg/mL control yogurt, and the MYH group received MFE orally by feeding them with 30 mg/mL symbiotic yogurt using a gavage method. On the basis of our previous study, the fasting glucose, oral glucose tolerance test, insulin, and homeostatic model assessment for insulin resistance results were reported in Ban et al (2020a).…”
Section: Animal Modelsmentioning
confidence: 99%
“…A symbiotic yogurt is a yogurt containing prebiotics and probiotics (Schrezenmeir and de Vrese, 2001). Previous studies have reported that the consumption of symbiotic yogurt is beneficial for the treatment of T2DM (Pandey et al, 2015;Ban et al, 2020a). However, a high-sugar content is added to lowsugar fermented dairy products, particularly yogurts, to improve their taste (Gijsbers et al, 2016;Wan et al, Effect of symbiotic yogurt fortified with monk fruit extract on hepatic lipid biomarkers and metabolism in type 2 diabetes rats Qingfeng Ban, 1,2 Xiaomeng Sun, 1 Yunqing Jiang, 1 Jianjun Cheng, 1 * and Mingruo Guo 3 * 2021).…”
Section: Introductionmentioning
confidence: 99%